Investigating the Clitellata (Annelida) of Icelandic springs with alternative barcodes - Klinth, Mårten; Kreiling, Agnes-Katharina; Erseus, Christer (Fauna norvegica, 2019)
DNA barcoding is an invaluable tool to identify clitellates, regardless of life stage or cryptic morphology. However, as COI (the standard barcode for animals) is relatively long (658 bp), sequencing it requires DNA of high quality. When DNA is fragmented due to degradation, alternative barcodes of shorter length present an option to obtain genetic material. We attempted to sequence 187 clitellates sampled from springs in Iceland. However, the material had been stored at room temperature for two years, and DNA of the worms had degraded, and only three COI sequences were produced (i.e., <2% success rate). Using two alternative barcodes of 16S (one ca. 320 bp, the other ca. 70 bp long) we increased the number of sequenced specimens to 51. Comparisons of the 16S sequences showed that even the short 70 bp fragment contained enough genetic variation to separate all clitellate species in the material. Combined with morphological examinations we recognized a total of 23 species, where at least 8 are new records for Iceland, some belonging to genera new for Iceland: Cernosvitoviella and Pristina. All the new taxa are included in an updated species list of Icelandic Clitellata. The material revealed some stygophilic species previously known to inhabit springs, but true stygobionts, which are restricted to groundwater habitats, were not found. Our study shows that short 16S fragments can be obtained from DNA too degraded to be used in traditional COI barcoding, and contain enough genetic variation to separate closely related clitellate species.
Includes an updated list of Icelandic Clitellata with references